PTU-055 Comparative cost-effectiveness of gastroesophageal reflux disease (GORD) centric and population based barrett's oesophagus (BO) screening. (June 2019) - Sami, Sarmed; Moriarty, James; Rosedahl, Jordan; Borah, Bijan; Kisiel, John; Katzka, David; Wang, Kenneth; Ahlquist, David; Iyer, Prasad
Abstract : Introduction: With the development of minimally invasive tests for BO, the prospect of population screening (all adults age ≥50) instead of targeted screening (white, male, age ≥50, GORD) has arisen. We aimed to evaluate the comparative cost effectiveness of current tests utilising recently published data on prevalence, accuracy, screening uptake, and costs. Methods: Decision analytic methods were conducted using Markov Modeling. The simulation compared six screening strategies to no screening: sedated OGD (sOGD, Cytosponge with TFF3 biomarker, Sponge on String (SoS) with methylated DNA markers, breath testing (E-Nose), hospital-based transnasal endoscopy (hTNE), and mobile unit-based transnasal endoscopy (mTNE). The model simulated a hypothetical cohort of 100, 000 individuals aged ≥50 followed up for 40 years. sOGD was used as a confirmatory test of positive findings for all other diagnostic tests. Mean costs (direct as well as indirect costs resulting from missed or false positive diagnoses and low test uptake) were calculated for each strategy. Quality of life outcomes were based on quality adjusted life years (QALYs). Results: Screening (GORD centric and population) was associated with small gains in QALYs compared to no screening (table 1 ). Under the general population analysis, mean costs ranged from $120 (mTNE) to $554 (E-Nose). While mTNE was the dominant strategy, both the Cytosponge and SoS tests had the lowest incremental cost effectiveness ratios (ICERs) (table 1 ). Under the GORD centric screening analysis, mean costs ranged from $212 (mTNE) to $768 (E-Nose). Cytosponge, SoS, hTNE, and mTNE were all dominant strategies compared to no screening. Out of those, mTNE was the least costly and most effective strategy. The E Nose test had the highest ICER primarily due to lower accuracy estimates. Conclusions: While mTNE was the dominant strategy for both screening scenarios, this technique is not widely utilised and has been only evaluated in one centre. The Cytosponge and SoS strategies had very favourable ICERs in both strategies and may make population based BO screening regardless of GORD status feasible.